Uremia and Inadequate Oxygen Supply Induce Eryptosis and Intracellular Hypoxia in Red Blood Cells - Dias, Gabriela Ferreira; Tozoni, Sara Soares; Bohnen, Gabriela; Grobe, Nadja; Rodrigues, Silvia D; Meireles, Tassiana; Nakao, Lia S; Pecoits-Filho, Roberto; Kotanko, Peter; Moreno-Amaral, Andréa Novais (Cellular physiology and biochemistry, 2021)
BACKGROUND/AIMS: Chronic kidney disease is frequently accompanied by anemia, hypoxemia, and hypoxia. It has become clear that the impaired erythropoietin production and altered iron homeostasis are not the sole causes of renal anemia. Eryptosis is a process of red blood cells (RBC) death, like apoptosis of nucleated cells, characterized by Ca2+ influx and phosphatidylserine (PS) exposure to the outer RBC membrane leaflet. Eryptosis can be induced by uremic toxins and occurs before senescence, thus shortening RBC lifespan and aggravating renal anemia. We aimed to assess eryptosis and intracellular oxygen levels of RBC from hemodialysis patients (HD-RBC) and their response to hypoxia, uremia, and uremic toxins uptake inhibition. METHODS: Using flow cytometry, RBC from healthy individuals (CON-RBC) and HD-RBC were subjected to PS (Annexin-V), intracellular Ca2+ (Fluo-3/AM) and intracellular oxygen (Hypoxia Green) measurements, at baseline and after incubation with uremic serum and/or hypoxia (5% O2), with or without ketoprofen. Baseline levels of uremic toxins were quantified in serum and cytosol by high performance liquid chromatography. RESULTS: Here, we show that HD-RBC have less intracellular oxygen and that it is further decreased post-HD. Also, incubation in 5% O2 and uremia triggered eryptosis in vitro by exposing PS. Hypoxia itself increased the PS exposure in HD-RBC and CON-RBC, and the addition of uremic serum aggravated it. Furthermore, inhibition of the organic anion transporter 2 with ketoprofen reverted eryptosis and restored the levels of intracellular oxygen. Cytosolic levels of the uremic toxins pCS and IAA were decreased after dialysis. CONCLUSION: These findings suggest the participation of uremic toxins and hypoxia in the process of eryptosis and intracellular oxygenation.